Increasing scientific literacy in the inheritance and biotechnology chapter by implementing problem-based learning - Aisyah, Shonia Nur; Rahayu, Nunuk Cahya Eka; Zainuddin, Abu (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research aims to increase students' scientific literacy at SMPN 2 Buduran by implementing problem-based learning. The method used is two cycles of CAR. As a result, in the context aspect of cycle I, 60% of students got a score of B, which increased in cycle II to 62.9% of students got a score of A. In the content aspect of cycle I, 66% got a score of B, then experienced an increase in cycle II, as many as 57.2% of students got a score of A. In the competency aspect of cycle I, as many as 51.6% of students got a score of C; this increased in cycle II, as many as 60% got a score of B. The increase in scientific literacy can be seen in the increase in student learning outcomes. In cycle I, the average class score on the pre-test was 66.2 with a completion percentage of 11.4%, then increased on the post-test with an average class score of 79.4 and a completion percentage of 68.5%. In cycle II, the average class score on the pre-test increased rapidly to 78, with a completion percentage of 62.8%. Then, in the post-test, it reached an average score of 91.4 and a completion percentage of 100%. Problem-based learning has been proven to increase student's scientific literacy.